Diabetic ketoacidosis with severe hypokalemia and persistent hypernatremia in an adolescent girl with COVID‐19 infection. Issue 2 (6th February 2022) - Badawy, Mohammed Kamal; Viswanath, Vidya; Khetriwal, Babita; Pradhan, Swati; Williams, Rachel M.; Pathan, Nazima; Marcovecchio, Maria Loredana
Abstract: We report a case of new‐onset type 1 diabetes in a girl presenting with severe diabetic ketoacidosis, complicated by profound hypokalemia and hypernatremia. We describe the clinical course, management challenges, and the potential role of the concomitant COVID‐19 infection in the complexity of this case. Abstract : COVID‐19 infection may have changed the presentation and severity of diabetic ketoacidosis (DKA) in children with type 1 diabetes. Significant electrolyte abnormalities are rare at DKA presentation but can lead to additional challenges to management.